Apocryphal Cicero: John Toland's Cicero Illustratus and Notions of Authority in the Early Enlightenment. - East, Katherine (International Journal of the Classical Tradition, 2016)
The article discusses author John Toland's "Cicero Illustratus" in which he addressed the issue of the surviving Ciceronian spuria in the context of his editorial endeavour and raise questions: which spurious works should he include, and how would he justify his decision. Toland states that the modern scholar is provided with a resource which provides a valuable account of the spurious works still present in the Ciceronian tradition. Toland also use a combination of their textual history.